THE EFFECT OF APTITUDE TREATMENT INTERACTION LEARNING MODEL ON MATHEMATICAL CREATIVE THINKING SKILLS - Yusak Wijaya Y; Gunawan Gunawan; Eka Setyaningsih; Jaka Wijaya Kusuma; Indira Pipit Miranti (International Journal of Multidisciplinary Research and Literature, 2023)
The study aimed to determine the effect of the implementation of the Aptitude Treatment Interaction learning model and its effectiveness on the mathematical thinking skills of SMPN 1 Ajibarang students on the topic of Opportunity, between the ATI (Aptitude Treatment Interaction) experimental class and the control class with the cooperative learning model. This type of research was a quasi-experimental design with two control experiment groups, a pre- test and a post-test design. The results showed differences in student learning outcomes between the two classes, as evidenced by the results of the t-test (2 parties), where the significance value was 0.009 0.025. Thus, there was an average difference between the experimental and the control classes. So, the application of the ATI (Aptitude Treatment Interaction) learning model in the experimental class affects the creative thinking ability of SMP for eighth grader students on the subject of opportunity compared to the control class